Reconocimiento del patrimonio, caso de estudio la peña, Cundinamarca (2022)
The subject of study is focused on the deterioration of cultural heritage and its characteristics, present in small municipalities, category 6, and their rural outskirts, where there is evidence of loss of identity and cultural roots, in the same way the little investment earmarked for the conservation of the cultural heritage of each region. The study faces the problem of how to favor the appropriation and exaltation of the culture and characteristic features of the rural regions of the country, contextualized in the municipality of La Peña, in the province of Gualivá, to the northwest of the department of Cundinamarca. A territory marked by years of violence in the country and a municipality where the loss of tangible and intangible heritage is constant.